MENINGKATKAN KEMAMPUAN MENGENAL HURUF MELALUI METODE FONIK BAGI ANAK TUNARUNGU SEDANG (Single Subject Research Kelas I di SLB Negeri Kota Sungai Penuh) - Oriza Wulandari Risti (Jurnal Penelitian Pendidikan Khusus, 2012)
This study started from the problems that researchers find in SLB Negeri Kota Sungai Penuh Kerinci that deaf children were grade 1 does not recognize the letters (a, b, c, d, e, f). based on this, this study aims to improve children's ability to recognize letters correctly. The hypothesis in this study is Fonik method can enhance the ability for deaf children recognize the letters were X-class 1 in the SLB Negeri Kota Sungai Penuh Kerinci. Type of research is experimental approach in the form of single-subject research (SSR), using AB research design. Subject of this study is a deaf child being, the assessment takes the form number that is how many letters can be mentioned, shown and written observations of the child at any time. This study first look at the condition of children in recognizing letters baseline, after treatment given investigators re-measure the number of letters that can be described, demonstrated and written correctly. The data obtained were processed with the graph so that the results can be drawn between the conditions. The results of this study indicate that the ability of deaf children recognize the letters are in the increase. In the baseline phase the child is only able to recognize one letter, is seen in the third observation to observation seventh. After intervention by using fonik seen that an increase in the child recognize the letters correctly as follows: a, b, c, d, e, f. Thus the hypothesis is accepted that fonik method can be used to improve the ability for deaf children recognize the letters were in SLB Negeri Kota Sungai Penuh Kerinci, the researchers suggested that further research in order to utilize the method fonik to raise the children's ability to recognize letters.